2018
DOI: 10.1007/s12041-018-0896-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci mapping for stomatal traits in interspecific hybrids of Eucalyptus

Abstract: Eucalyptus is an important industrial species with tolerance to drought and salt stress. Genetic improvement activities including quantitative trait loci (QTL) mapping for pulping and adventitious rooting traits are in progress, but no information is available on the genomic regions on adaptive traits such as stomatal characteristics. In this study, an interspecific cross between Eucalyptus tereticornis and E. grandis was generated for the development of genetic map and QTL identification for stomatal traits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
6
2
Order By: Relevance
“…These results demonstrate the superiority of current GBS technology in the genetic map construction for Eucalyptus . The marker density of our E. urophylla map and consensus map were slightly lower than that recently reported in E. urophylla (1773 SNPs with 885.9 cM) ( Bartholomé et al., 2015 ) and the consensus map of E. grandis × E. urophylla (2290 markers with 1107.6 cM) ( Kullan et al., 2012 ), however, the E. tereticornis map constructed here is the densest to date (such as, 585 markers with 1241.4 cM in Li et al., 2015 ; 204 markers with 1023.56 cM in Sumathi et al., 2018 ). Generally, the density of maps constructed here also compare favourably with recent GBS- or restriction site-associated sequencing (RAD-seq) maps for other forest species.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…These results demonstrate the superiority of current GBS technology in the genetic map construction for Eucalyptus . The marker density of our E. urophylla map and consensus map were slightly lower than that recently reported in E. urophylla (1773 SNPs with 885.9 cM) ( Bartholomé et al., 2015 ) and the consensus map of E. grandis × E. urophylla (2290 markers with 1107.6 cM) ( Kullan et al., 2012 ), however, the E. tereticornis map constructed here is the densest to date (such as, 585 markers with 1241.4 cM in Li et al., 2015 ; 204 markers with 1023.56 cM in Sumathi et al., 2018 ). Generally, the density of maps constructed here also compare favourably with recent GBS- or restriction site-associated sequencing (RAD-seq) maps for other forest species.…”
Section: Discussioncontrasting
confidence: 86%
“…The publication of the E. grandis reference genome ( Myburg et al., 2014 ) has also significantly aided QTL mapping efforts, with high synteny between E. grandis and other common commercial eucalypts. In Eucalyptus , most of the previous QTL studies found few substantive associations between target traits and candidate genes due to the low resolution of genetic map, large QTL interval, or lack of reference genomic information ( Freeman et al., 2009 ; Thumma et al., 2010 ; Freeman et al., 2013 ; Sumathi et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The number and strength of QTL identified for leaf gas exchange traits (1–4 QTL per trait in a single experiment) were similar to previous studies of those traits ( Hervé et al, 2001 ; Teng et al, 2004 ; Pelleschi et al, 2006 ). In contrast, a greater number of QTL were identified for many of the stomatal patterning traits (e.g., PD—7, SI—9, SCA—9, SCD—9, SCTA—7 QTL in a single experiment) than in previous studies ( Patto et al, 2003 ; Hall et al, 2005 ; Laza et al, 2010 ; Schoppach et al, 2016 ; Shahinnia et al, 2016 ; Liu et al, 2017 ; Sumathi et al, 2018 ; Delgado et al, 2019 ; Prakash et al, 2020 ). This larger number of significant QTL was linked to more small-effect QTL (PVE < 10%) being successfully identified.…”
Section: Discussionmentioning
confidence: 73%
“…Linkage mapping in barley ( Hordeum vulgare ), wheat ( Triticum aestivum ), and rice ( Oryza sativa ) has discovered quantitative trait loci (QTL) that are associated with stomatal patterning traits ( Patto et al, 2003 ; Laza et al, 2010 ; Liu et al, 2014 , 2017 ; Sumathi et al, 2018 ), including some that colocalize with yield QTL ( Shahinnia et al, 2016 ). But, the only reports of similar experiments in maize predate statistical techniques, such as QTL mapping ( Heichel, 1971 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers, such as Takahashi [5], Peel [6], and Sumathi [7], used manual counting in their studies to determine the number of epidermal stomata. This approach is obviously tedious and labour‐intensive, and errors and omissions are prone to occur when the number of pores is large.…”
Section: Introductionmentioning
confidence: 99%